2019
DOI: 10.1152/jn.00062.2019
|View full text |Cite
|
Sign up to set email alerts
|

Overlapping and distinct contributions of stimulus location and of spatial context to nonspatial visual short-term memory

Abstract: Stimulus location is not always informative during visual short-term memory (VSTM) for nonspatial features. Nevertheless, there is considerable evidence for the automatic encoding and retention of location information, regardless of its task relevance. To explore the functional and neural bases of the representation of spatial context in VSTM for nonspatial information, functional magnetic resonance imaging was performed while subjects performed delayed recall for the orientation of individual stimuli. Stimulu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
31
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 32 publications
(37 citation statements)
references
References 29 publications
6
31
0
Order By: Relevance
“…For “PMI-trained IEMs,” the data on each trial were labeled according to the identity of the PMI at the time point of interest, and the converse was true for “UMI-trained” IEMs. Results from the PMI-trained IEMs would be the primary focus of this study because PMI-trained models have been shown to be valid and robust for various brain regions, including occipitotemporal cortex, IPS, and FEF [ 21 23 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…For “PMI-trained IEMs,” the data on each trial were labeled according to the identity of the PMI at the time point of interest, and the converse was true for “UMI-trained” IEMs. Results from the PMI-trained IEMs would be the primary focus of this study because PMI-trained models have been shown to be valid and robust for various brain regions, including occipitotemporal cortex, IPS, and FEF [ 21 23 ].…”
Section: Resultsmentioning
confidence: 99%
“…When tested with UMI-labeled data, reconstructions from this PMI-trained IEM would index the extent to which the representational format of the UMI was similar to that of the PMI. Results from the PMI-trained IEMs would be the primary focus of this study because PMI-trained models have been shown to be valid and robust for various brain regions, including occipitotemporal cortex, IPS, and FEF [ 21 23 ]. For UMI-trained IEMs, the IEM was trained on data labeled according to the identity of the UMI and tested on data labeled according to the identity of the both the PMI and the UMI.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…That is, if one or more neural codes are engaged uniquely by the MSR task, our approach would not be sensitive to this. Nonetheless, our experience from previous studies (e.g., Cai, Sheldon, Yu, & Postle, 2019;LaRocque et al, 2017) gave us confidence that this approach would be effective at testing our principal hypotheses of interest.…”
Section: Designmentioning
confidence: 92%
“…The results reported here are from analyses carried out on existing data collected for other purposes [19,20]. Thirty individuals (10 males, mean age 20.7 ± 2. were displayed with equal spacing along the response wheel, and subjects registered their memory of the sample orientation by moving the cursor to the appropriate location on the response wheel and registering that location with a button press.…”
Section: Subjectsmentioning
confidence: 99%